Paraoxonase and Arylesterase Activities, Lipid Profile, and Oxidative Damage in Experimental Ischemic Colitis Model - Ethem Unal; Cengiz Eris; Bülent Kaya; Hafize Uzun; Faruk Cavdar; Murat Yildar; Ali Riza Kiziler; Birsen Aydemir; Pembegul Gunes; Riza Kutanis; Izzet Titiz (Gastroenterology Research and Practice)
Objective. In the present study, since PON1 is known as an HDL-associated antioxidant enzyme that inhibits the oxidative modification of LDL and oxidative stress plays a role in the pathogenesis of mesenteric ischemia, we investigated the changes in PON1 activity and lipid profile in an experimental ischemic colitis model. Methods. Forty male Wistar albino rats were divided into two groups: the control group (N=15) and the experimental group (N=25). All animals were anesthetized with ether and ketamine anesthesia to undergo a midline laparotomy. Ischemic colitis was induced by marginal vessel ligation in the splenic flexura (devascularization process). A sham laparotomy was performed in the control group. All animals were sacrificed on the seventh postoperative day. Oxidative stress marker (malonyldialdehyde, MDA), lipid profile, and paraoxonase (PON-1) and arylesterase activities were determined. Histopathological evaluation was done under light microscopy, after sectioning and staining with hematoxyline and eosin. Statistical analysis was conducted using Student’s t-test and Mann-Whitney U test, and P<0.05 was considered as statistically significant. Results. There was a significant decrease in both serum and tissue PON1 activity in ischemic colitis group (P<0.01, for each). Similarly, arylesterase levels showed a parallel decrease in both tissue and serum of the experimental group (P<0.01 and P<0.001, retrospectively). MDA, an oxidative stress marker, was seen to increase in the experimental group (P<0.01, tissue; P<0.05, serum). In experimental group, there was a significant rise in serum total cholesterol and LDL levels (P<0.001, for each). However, HDL level decreased significantly (P<0.001). Triglycerides did not show any change between the groups (P>0.05). Conclusions. PON1 and arylesterase play an important role in the pathophysiology of ischemic colitis.